2018
DOI: 10.1155/2018/8973581
|View full text |Cite
|
Sign up to set email alerts
|

A New GNB Model of Crash Frequency for Freeway Sharp Horizontal Curve Based on Interactive Influence of Explanatory Variables

Abstract: Crash prediction of the sharp horizontal curve segment of freeway is a key method in analyzing safety situation of freeway horizontal alignment. The target of this paper is to improve predicting accuracy after considering the elastic influence of explanatory variables and interaction of explanatory variables on crash rate prediction. In the paper, flexibility and elasticity are defined to express the elastic influence of explanatory variables and interaction of explanatory variables on crash rate prediction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…(1) Turning beneft ratio: Te turning beneft ratio TBR as a classifcation indicator refers to the ratio of the trajectory's approximate radius to the ideal radius, as shown in equation (7). According to the coordinates of the starting point (x s , y s ), midpoint (x m , y m ), and endpoint (x e , y e ) of the trajectory in the x-y coordinate system, the approximation radius R T can be computed using Heron's formula [58], as shown in equation (8).…”
Section: Classifcation Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Turning beneft ratio: Te turning beneft ratio TBR as a classifcation indicator refers to the ratio of the trajectory's approximate radius to the ideal radius, as shown in equation (7). According to the coordinates of the starting point (x s , y s ), midpoint (x m , y m ), and endpoint (x e , y e ) of the trajectory in the x-y coordinate system, the approximation radius R T can be computed using Heron's formula [58], as shown in equation (8).…”
Section: Classifcation Indicatorsmentioning
confidence: 99%
“…Te reasons behind the frequent crashes under rainy conditions not only lie in the reduced skid resistance leading to longer braking distances for vehicles but also in the fact that vehicles easily sideslip on curved segments [5]. Previous studies have shown that rainfall can increase the expected number of severe crashes on curved segments by 3.26 times [6,7]. Terefore, comprehending the impact of rainfall on vehicle sideslip risk on curved segments is crucial for enhancing road design and trafc safety management.…”
Section: Introductionmentioning
confidence: 99%
“…e configuration and alignment of the road also have a greater impact on traffic safety. Wang et al [18,19] analyzed the road safety of expressways and highways under different alignment combination conditions. erefore, in the present paper, the common weaving area configuration, that is, a three-lane and ramp double-in, single-out urban interchange with auxiliary lanes, is analyzed in this paper [20].…”
Section: Introductionmentioning
confidence: 99%